Literasi Statistis Siswa SMP Berkemampuan Statistika Tinggi dalam Menyelesaikan Soal Numerasi - Dewi Pujiati; Masriyah Masriyah; Yurizka Melia Sari (Universitas Negeri Surabaya, 2026)
Statistical literacy is the process of understanding statistical data or information, processing statistical data or information, interpreting the results of data processing, and evaluating answers. Statistical literacy is important in processing information to make decisions and conclusions. This research adopts a qualitative approach with a case study design aimed at describing the statistical literacy of junior high school students with high statistical ability in solving numeracy problems. The research subject is a student with high statistical ability based on a statistical ability test. The indicators of statistical literacy in this study are understanding statistical data or information, processing statistical data or information, interpreting the results of data processing, and evaluating answers. The results show that students with high statistical ability solve numeracy problems by understanding statistical data or information well, processing statistical data or information accurately and systematically, interpreting the results of data processing, and always evaluating answers by recalculating. Teachers are advised to encourage students to evaluate their answers by checking them again, not only by counting them again but also by checking the entire answer in order to obtain the correct answer.